2022
DOI: 10.3390/jcm11206167
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Dry Needling with a Standard Exercise Program on Pain and Quality of Life in Patients with Chronic Mechanical Neck Pain

Abstract: Background: This study aimed to determine the short-term effects of dry needling (DN) combined with a standard exercise program on pain and quality of life in patients with chronic mechanical neck pain (CMNP). Methods: Thirty-one patients with CMNP were randomly allocated to the experimental and control groups. The experimental group received DN and underwent a standard exercise program (one DN session and six exercise sessions) for two weeks, whereas the control group underwent the same exercise program alone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…In this study, the results of the SF-36 showed that intervention had no significant effect on improvement of patient's quality of life, which agrees with the results of some previous studies. In the study of Gerber et al [ 119 ], and Almushahhim et al [ 120 ], the effects of DN on the treatment of neck pain were investigated. The results of these two studies did not show a significant difference for the SF-36 scores of the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the results of the SF-36 showed that intervention had no significant effect on improvement of patient's quality of life, which agrees with the results of some previous studies. In the study of Gerber et al [ 119 ], and Almushahhim et al [ 120 ], the effects of DN on the treatment of neck pain were investigated. The results of these two studies did not show a significant difference for the SF-36 scores of the two groups.…”
Section: Discussionmentioning
confidence: 99%